Flavonoids from Kalanchoe ×laetivirens Impair Survival and Immunity of Atta sexdens (Hymenoptera: Formicidae) - Silva Melo, Márcio; Santos Silva, Cynthia L.; Tenório, Amanda Caroline Teles; Silva Melo, Bruno; da Silva Barbosa, Rone; Sarmento, Renato Almeida; Holzbach, Juliana Cristina; Barbosa Cruz, Állefe; Nascimento, Isabele Rodrigues; de Souza, Danival José (Natural Products Journal, The, 2024)
Background: The active secondary metabolites of various Kalanchoe species are promising for controlling insects and other agricultural pests. Objective: This study aimed to evaluate the mortality and immune responses of the leafcutter ant Atta sexdens (L.) after treatment with Kalanchoe ×laetivirens (Desc.) aqueous extract. The effects on an aquatic organism used as a bioindicator, Chironomus xanthus (Rempel), were also evaluated. Methods: Different K. ×laetivirens concentrations were prepared by dilution in honey to assess the toxicity and determine the median lethal concentration (LC50) for A. sexdens workers. The haemocytes of workers treated with a sublethal concentration (0.005 g/mL) were counted. Results: The plant extracts induced high mortality in A. sexdens workers. All concentrations, except 0.001 g/mL, increased mortality rates. The sublethal concentration negatively affected the immune system of A. sexdens workers 48 and 72 h after ingestion. The flavonoids 4
Keywords: forests